Home Visit sebagai Pendukung Penanganan Permasalahan Siswa SMA - Rahmiyati, Evi; Salsabilla, Elvira; Martunis, Martunis; Marsela, Fitra (Universitas Negeri Makassar, 2025)
This study aims to examine the implementation of home visit services in guidance and counseling at SMAN 12 Banda Aceh. The method used was qualitative research with a descriptive approach. The study subjects consisted of two guidance and counseling teachers, three homeroom teachers, and one principal. Data collection techniques included interviews and documentation, using a structured interview guide and a document recording format as instruments. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that home visit services are implemented by guidance and counseling teachers in collaboration with homeroom teachers to understand student problems and establish communication with parents. Obstacles identified included poor initial communication with students, the lack of an official assignment letter from the principal, and limited operational funds for home visits. Supporting factors, such as a warm welcome from parents and a supportive environment, contributed to the program's success. The novelty of this study demonstrates that the success of home visit services depends not only on formal administrative support but also on emotional engagement and active communication between teachers, students, and parents. The guidance and counseling teacher's initiative in building interpersonal relationships is crucial in the implementation of this service.